2013
DOI: 10.1038/ejcn.2013.219
|View full text |Cite
|
Sign up to set email alerts
|

Examining the content of weight, nutrition and physical activity advices provided by Dutch practice nurses in primary care: analysis of videotaped consultations

Abstract: Weight advices often related to the patient's complaint. PNs seldom set a concrete weight goal. Although benefits of physical activity were discussed, often no practical advices were provided about how to achieve this. Integrated lifestyle advice was not common: advices about nutrition and physical activity were fragmented throughout the consultation. Obesity prevention needs more emphasis in PNs' educational programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
50
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 59 publications
4
50
0
2
Order By: Relevance
“…Integrated lifestyle advice was not common: advices about nutrition and physical activity were fragmented throughout the consultation. The conclusion is clear: obesity prevention needs more emphasis in educational programmes of PNs (158). We also assessed the quality of weight loss counseling by Dutch PNs to overweight and obese patients, including both PNs' compliance with the Five A's Model for behavioral counselling in primary care (33) and the use of different communication styles (159).…”
Section: Practice Nurses (Pns) In Primary Carementioning
confidence: 99%
See 1 more Smart Citation
“…Integrated lifestyle advice was not common: advices about nutrition and physical activity were fragmented throughout the consultation. The conclusion is clear: obesity prevention needs more emphasis in educational programmes of PNs (158). We also assessed the quality of weight loss counseling by Dutch PNs to overweight and obese patients, including both PNs' compliance with the Five A's Model for behavioral counselling in primary care (33) and the use of different communication styles (159).…”
Section: Practice Nurses (Pns) In Primary Carementioning
confidence: 99%
“…Together with Noordman and Van Dulmen (NIVEL), Van Dillen and I carried out research on PNs. We examined the content of weight, nutrition, and physical activity advices provided by Dutch PNs through an analysis of video-taped consultations (158). Lose weight, eat less fat, and be more physically active in general were the main categories for each type of advice.…”
Section: Practice Nurses (Pns) In Primary Carementioning
confidence: 99%
“…A recent study showed that practice nurses seem to fail to adequately emphasize this advice (27) . However, studies among general practitioners showed that their actual nutrition guidance practices are not only determined by predisposing factors and driving forces, but also by perceived barriers (28)(29)(30)(31)(32)(33)(34)(35)(36)(37) .…”
mentioning
confidence: 99%
“…In our prior research project, we examined the content of practice nurses' advice to patients with overweight or obesity (27) . The aim of the present study was to identify points for improvement in the quality of weight-loss counselling by practice nurses to patients with overweight or obesity.…”
mentioning
confidence: 99%
“…23,24 Audio-taping and videotaping of consultations 25,26 are being increasingly used to explore the management of diabetes [27][28][29][30][31] and antecedents such as overweight and obesity. 32 Further research has been called for, 23 including exploration of physicians and patients "talking past one another" 33 and interactions between nonphysician health care professionals and patients.…”
mentioning
confidence: 99%